Managing the combined consequences of COVID-19 infection and lock-down policies on athletes: narrative review and guidelines proposal for a safe return to sport - Fabre, J.-B.; Grelot, L.; Vanbiervielt, W.; Mazerie, J.; Manca, R.; Martin, V. (BMJ Open Sport & Exercise Medicine, 2020)
COVID-19 pandemic is a global health matter. The disease spread rapidly across the globe and brought the world of sports to an unprecedented stoppage. Usual symptoms of the disease are fever, cough, myalgia, fatigue, slight dyspnoea, sore throat and headache. In more severe cases, dyspnoea, hypoxaemia, respiratory failure, shock and multiorgan failure occur. This appears to be a self-limiting phenomenon related to individuals with coexisting medical conditions, such as hypertension, diabetes and cardiovascular disorders. Nevertheless, cases have been reported in professional soccer players in extremely good fitness condition, demonstrating that athletes are not spared by the disease. Despite COVID-19 clinical manifestations are mainly respiratory, major cardiac complications are being reported, leading to acute myocarditis. One difficulty is that symptoms of COVID-19 vary among individuals, with athletes being affected with no apparent sign of the disease. This could be a real danger for amateur or professional athletes when returning to their usual training and thus to play. Another threat is that the lock-down policies did not allow most athletes to follow their usual training routines. There is thus a need for a careful approach by the sports medicine community to ensure safety of all athletes before they return to sport. Here, we propose evaluation guidelines of fitness and health of athletes to (1) reduce any lethal risk of practice, especially myocarditis and sudden cardiac death; (2) evaluate the combined consequences of the disease and detraining on the physical abilities and biological profile of athletes; and (3) monitor postinfection fatigue symptoms.